The 5th International Congress of CiiEM (IC CiiEM) 2021
DOI: 10.3390/msf2021005012
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Risk Assessment in Victims Information and Assistance Office

Abstract: The purpose of this paper is to demonstrate the work developed by the Victims Information and Assistance Office (GIAV), and its role as technical advisor to the Lisbon Public Prosecutor’s Office, specifically about Intimate Partner Violence (IPV) risk assessment. GIAV plays a key role in assisting the Public Prosecutor’s Office as the main response to cases with higher complexity and it provides support about measures to protect victims. The sample (n = 258) is derived from the IPV risk assessments of GIAV. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…When analyzing the dynamics between gender and violence, several researchers have shown that power dynamics is a complex phenomenon that can derive from individual, situational, cultural, and social factors (Vieraitis et al 2008;Neves and Almeida 2020). These studies have shown that men's domination and IPV tolerance and legitimation are a more prominent presence in the male gender due to the existence of patriarchal societies, where the belief that men have a social and cultural ascendant over women favors the development and maintenance of beliefs favorable to IPV (Almeida et al 2021;Carlson and Worden 2005;Machado et al 2014).…”
Section: Sociocultural Issues and Gendermentioning
confidence: 99%
“…When analyzing the dynamics between gender and violence, several researchers have shown that power dynamics is a complex phenomenon that can derive from individual, situational, cultural, and social factors (Vieraitis et al 2008;Neves and Almeida 2020). These studies have shown that men's domination and IPV tolerance and legitimation are a more prominent presence in the male gender due to the existence of patriarchal societies, where the belief that men have a social and cultural ascendant over women favors the development and maintenance of beliefs favorable to IPV (Almeida et al 2021;Carlson and Worden 2005;Machado et al 2014).…”
Section: Sociocultural Issues and Gendermentioning
confidence: 99%